Sensing Properties of a Fabry-Perot Dielectric Structure and Dimer Nanoparticles - A. Polemi; K. L. Shuford (Journal of Nanotechnology)
We investigate the use of a Fabry-Perot dielectric structure combined with differently shaped nanoparticles for Surface Enhanced Raman Scattering. In particular, we show how an ideal two-layer Fabry-Perot configuration enhances the local surface field of silver nanoparticles positioned on the surface of the structure. We develop the concept using disc dimers and then extend the discussion to bowtie nanoparticles. The structure is excited by a single emitter, which couples to the nanoparticles through the dielectric layers, producing a wide aperture field that can be used to excite multiple dimers. We show how an array of nanoparticles can be properly arranged in order to increase the total scattering signal generated from the structure. The layered geometry produces robust field properties in between nanoparticles, making the overall sensing characteristics less sensitive to the interparticle seperation distance and incident polarization.